2022
DOI: 10.1097/gox.0000000000004443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality and Reliability of Gender-affirming Surgery Videos on YouTube and TikTok

Abstract: Background: Social media platforms have changed the way medical information is disseminated. Transgender patients may utilize social media to learn about gender-affirming surgery (GAS). Although videos on social media are readily accessible, their content is not verified or peer-reviewed. Therefore, this study aimed to evaluate the quality and reliability of YouTube and TikTok videos related to GAS. Methods: YouTube and TikTok were queried for gender-affirming top surgery, metoidioplasty, phalloplasty, breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, these findings are consistent with previous studies which have found comparably low DISCERN scores when evaluating content on YouTube about other otolaryngologic topics such as cholesteatoma, 26 hypoglossal nerve stimulation, 27 trigeminal neuralgia, 28 and functional endoscopic sinus surgery. 29 Low quality and reliability of content on YouTube has been reported in other specialties as well, 30,31 although videos about osteoporosis and keratoconus have been found to be of higher quality. 32,33 Thus, while it is certainly possible for health-related videos to be of high quality, video topics meeting this requirement are the exception, not the norm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings are consistent with previous studies which have found comparably low DISCERN scores when evaluating content on YouTube about other otolaryngologic topics such as cholesteatoma, 26 hypoglossal nerve stimulation, 27 trigeminal neuralgia, 28 and functional endoscopic sinus surgery. 29 Low quality and reliability of content on YouTube has been reported in other specialties as well, 30,31 although videos about osteoporosis and keratoconus have been found to be of higher quality. 32,33 Thus, while it is certainly possible for health-related videos to be of high quality, video topics meeting this requirement are the exception, not the norm.…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite widespread prior investigations into the quality and credibility of YouTube videos for patient decision-making and health care professional education, there is a lack of research applying this framework to laryngectomy content. [15][16][17] Given the potential benefits and drawbacks of YouTube to educate patients, it is critical to understand its effectiveness in accurately educating patients seeking treatment information about laryngectomy. Thus, we aim to assess the quality and reliability of laryngectomy content on YouTube to understand factors impacting the quality of content available to patients.…”
mentioning
confidence: 99%
“…Weil et al aggregate the scores of questions 1–15 (ranging from 16 to 75) to make the following interpretations: 63–75 denotes excellent, 51–62 denotes good, 39–50 denotes fair, 27–38 denotes poor, and 15–26 denotes very poor 20 . Another study done by Song et al interprets individual Likert scores with scores 4.5 and higher considered excellent, 4.2–4.4 considered very good, 3.4–4.1 good, 2.6–3.3 average, 1.9–2.5 poor, and <1.8 very poor 21 . Language discussing scores in the results section uses interpretations from Weil et al and Song et al where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have examined the reliability of gender-affirming surgery content on social media, but few have examined the veracity of information on facial feminization (FF) specifically. 4 Demand for FF surgery is increasing each year, and access continues to increase as more surgeons train in these techniques. 5 Expanding demand and increased availability of FF surgery, in an environment of unprecedented reliance on social media for medical information, necessitate thoughtful consideration of how and where patients seek educational materials.…”
mentioning
confidence: 99%
“…The ease of information sharing has made social media an especially useful tool for the historically underserved transgender patient population. Prior studies have examined the reliability of gender-affirming surgery content on social media, but few have examined the veracity of information on facial feminization (FF) specifically 4 . Demand for FF surgery is increasing each year, and access continues to increase as more surgeons train in these techniques 5 .…”
mentioning
confidence: 99%